Helix-Coil Transition of Albumin-Bovine and Gelatin - Pukar Vidyarthi, Ram (Asian Journal of Chemistry, 2010)
Viscosity, hydrogen ion equilibria and specific optical rotation of albumin-bovine and gelatin in 8 M urea solution have been measured. The shape of a protein molecule easily changes by changing pH of the medium. Reduced viscosity increases with increasing pH of the medium upto a certain limit. After this limit, the viscosity decreases with the increase of pH. This is only because, at a certain pH value the concentration of ions in the solution increases sharply and they are attracted by the protein ions. This causes the screening of the chain charges, decreasing electrostatic repulsion and resulting in partial coiling of the protein molecules and hence in a decrease in viscosity of the solution. The different proteins have different pH region for helixcoil transition. Albumin-bovine and gelatin undergo helix-coil transition in the pH range of 6 and 3-4, respectively. Helix-coil transition takes place only in the states of denaturation.